Enhanced autophagy reversed aflatoxin B1-induced decrease in lactate secretion of dairy goat Sertoli cells - Shuaiqi Han; Hongyun Zhang; Xinyu Liu; Fei Wen; Baiyu Li; Zhiwen Bie; Hehan Qiu; Jianhong Hu (Ecotoxicology and Environmental Safety, 2023)
The deleterious effects of aflatoxins, especially aflatoxin B1 (AFB1) which are widespread at all stages of food production, on the reproductive system have been widely reported in males. However, it is still far from fully understood about the toxic effect and molecular mechanism after exposure to AFB1 in various testicular cells, especially Sertoli cells (SCs) which provide various energy materials and support to the developing germ cells as nurse cells. In this work, we examined the effects of AFB1 in dairy goat SCs on lactate production and autophagy, and the role of autophagy on AFB1-induced reduction in lactate production. Mechanistically, AFB1 destroyed the energy balance and reduced the secretion of lactate in dairy goat SCs (P < 0.01), resulting in a reduced level of ATP (P < 0.01) and phosphorylation of AMPK (P < 0.01). Subsequently, activated AMPK triggers autophagy by directly phosphorylating ULK1 (P < 0.05). The enhancement of autophagy partially reversed the AFB1-induced decrease in lactate secretion by promoting glucose utilization (P < 0.01) and increasing the expression of proteins related to lactate secretion in dairy goat SCs (P < 0.05) such as GLUT1, GLUT3, LDHA, and MCT4. Collectively, our study suggests that AFB1 inhibits the secretion of lactate which supply for germ cell development by damaging the ''Warburg-like'' metabolism of dairy goat SCs. Moreover, autophagy contributes to the resistance of glucose metabolism damage induced by AFB1. Data availability: All data generated or analyzed in this study are available from the corresponding authors upon request.